PENAMBAHAN FLY ASH BATU BARA PLTU SEBAGAI FILLER ASPAL AC WC (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2022)
The increasing population growth, the more vehicle users. This makes the government also have toimprove transportation services. One way is to improve the quality of asphalt in order to meet its servicelife. But the problem that is happening at this time is the difficulty of getting rock ash filler where in therules it is stated that fine aggregate (fly ash) must pass sieve no. 200 under 10%. This research mixed flyash as much as 1%, 2%, and 3%. The results of the study are the addition of fly ash from burning coalash as a filler for combustion residue from the Tanjung Enim PLTU for Asphalt Concrete WearingCourse (AC WC) asphalt mixture, the best results were obtained on a 2% mixture with the followingvalues: Stability value of 1240, 253 kg, VIM (Void In Mix) Value of 4.233%, VMA (Void in MineralAggregate) Value of 16.139%, VFB (Void Filled Bitumen) Value of 73.782%, Flow (melting) Value of3.63 mm and Marshall Quotient obtained at 329.280 kg/mm.